ORTHOTOPIC INTESTINOPLASTY OF URINARY BLADDER - A COMPLEX APPROACH - I. V. Semenyakin; M. I. Vasilchenko; D. A. Zelenin; A. M. Khazimov (Acta Biomedica Scientifica, 2012)
We analyzed the results of treatment of 57 patients who had. cystectomy with forming of orthotopic cystoplastte urinary bladder. Cystoplastis was performed by the original method. The approach to the choice of method, for creating orthotopic bladder was complex. Take into account the length of ileum resection, the technique of formation and the shape of the bladder, pre-calculated volume of orthotopic urinary bladder technique was used to create antireflux ureteral-intestinal anastomosis. Such an approach to reduce the risk of postoperative complications and to maintain the high, quality of life for patients.